Species composition and distribution of mangrove soil fungi from Iloilo River, Iloilo City, Philippines - Almoros, Peter Paul C.
Fungi are very diverse and ubiquitous microorganisms. Fungal diversity is an important aspect of the ecosystem that needs to be studied. There have been many studies regarding biodiversity of fungi in terrestrial, marine and riverine environments, but studies regarding fungi found in mangrove soil still needs to be done. This study focused on determining the species composition, distribution and ecology of mangrove soil fungi in the Iloilo River, Iloilo City. Soil Fungi were sampled from three areas in the river representing the downstream, midstream and upstream areas. Fungal isolates were identified based on morphological characteristics- cultural and microscopic features. There were 10 identified fungal species ?Aspergillus cf. flavus, Aspergillus cf. niger, Aspergillus cf. ustus, Aspergillus cf. versicolor, Aspergillus sp. (1), Aspergillus sp. (2) and Aspergillus sp. (3), Geotrichum cf. candidum, Penicillium cf. citrinum and Penicillium sp. (1), while there were 2 unidentified species. Three of these species were very frequent across the sites -Aspergillus cf. flavus, Geotrichum cf. candidum and Penicillium cf. citrinum.